ClpP of Streptococcus mutans Differentially Regulates Expression of Genomic Islands, Mutacin Production, and Antibiotic Tolerance - Chattoraj, Partho (American Society for Microbiology (ASM), 2010)
Streptococcus mutans is the primary etiological agent of human dental caries and, at times, of infective endocarditis. Within the oral cavity, the pathogen is subjected to conditions of stress. A well-conserved protein complex named ClpP (caseinolytic protease) plays a vital role in adaptation under stress conditions. To gain a better understanding of the global role of the ClpP protease in cellular homeostasis, a transcriptome analysis was performed using a ΔclpP mutant strain. The expression levels of more than 100 genes were up- or downregulated in the ΔclpP mutant compared to the wild type. Notably, the expression of genes in several genomic islands, such as TnSmu1 and TnSmu2, was differentially modulated in the ΔclpP mutant strain. ClpP deficiency also increased the expression of genes associated with a putative CRISPR locus. Furthermore, several stress-related genes and genes encoding bacteriocin-related peptides and many transcription factors were also found to be altered in the ΔclpP mutant strain. A comparative analysis of the two-dimensional protein profile of the wild type and the ΔclpP mutant strains showed altered protein profiles. Comparison of the transcriptome data with the proteomic data identified four common gene products, suggesting that the observed altered protein expression of these genes could be due to altered transcription. The results presented here indicate that ClpP-mediated proteolysis plays an important global role in the regulation of several important traits in this pathogen.